PENGARUH ALASAN PEMILIHAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI PADA MAHASISWA PRODI PENDIDIKAN EKONOMI FKIP UNTAN - Muhammad Faruq Azhar; Warneri Warneri; Okianna Okianna (Universitas Tanjungpura, 2018)
AbstractThis study aims to determine the influence of the reasons for choosing the price of purchasing decisions Xiaomi Smartphone to students of Economic Education Prodi FKIP UNTAN. The research method used is descriptive with the form of research relationship study. The respondents of this research are all students of FKIP UNTAN Education Economics Education Program students of 30 Xiaomi Smartphone users, by class of 2015, 2016 and 2017 Regular Class. Sampling technique in this research use saturated sampling technique. The results prove, that there is influence of the reasons for the selection of price decisions purchase Xiaomi Smartphone student student Economic Education Program FKIP UNTAN shown in the significance count 0.005 <α 0.05. The amount of coefficient of determination in this research is 24.6%, while the rest of 75.4% is influenced by independent variables not examined in this study, such as product quality, promotion and brand image..Keywords: Price, Purchase Decision, Xiaomi Smartphone